Heterogeneous SARS-CoV-2-Neutralizing Activities After Infection and Vaccination - Graninger, Marianne; Camp, Jeremy V.; Aberle, Stephan W.; Traugott, Marianna T.; Hoepler, Wolfgang; Puchhammer-Stöckl, Elisabeth; Weseslindtner, Lukas; Zoufaly, Alexander; Aberle, Judith H.; Stiasny, Karin (Frontiers in Immunology, 2022)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern (VOCs) with different resistance levels to existing immunity have recently emerged. Antibodies that recognize the SARS-CoV-2 spike (S) protein and exhibit neutralizing activities are considered the best correlate of protection and an understanding of humoral immunity is crucial for controlling the pandemic. We thus analyzed such antibodies in individuals recovered from infection in 2020 as well as vaccinees after two doses of an mRNA vaccine. Methods: Neutralizing antibody responses against three SARS-CoV-2 variants (D614G, VOCs Beta and Delta) were determined in serum samples from 54 infected individuals (24 non-hospitalized, 30 hospitalized) and 34 vaccinees shortly after symptom onset or second vaccination, respectively, as well as six months later. In addition, the effect of the S sequence of the infecting strain on neutralization was studied. Results: Non-hospitalized patients had the lowest neutralization titers against all variants, while those of hospitalized patients equaled or exceeded those of vaccinees. Neutralizing activity was lower against the two VOCs and declined significantly in all cohorts after six months. This decrease was more pronounced in hospitalized and vaccinated individuals than in non-hospitalized patients. Of note, the specific neutralizing activity (NT titer/ELISA value ratio) was higher in the infected cohorts than in vaccinees and did not differ between non-hospitalized and hospitalized patients. Patients infected with viral strains carrying mutations in the N-terminal domain of the spike protein were impaired in Beta VOC neutralization. Conclusions: Specific neutralizing activities were higher in infected than in vaccinated individuals, and no difference in the quality of these antibodies was observed between hospitalized and non-hospitalized patients, despite significantly lower titers in the latter group. Additionally, antibody responses of infected individuals showed greater heterogeneity than those of vaccinees, which was associated with mutations in the spike protein of the infecting strain. Overall, our findings yielded novel insights into SARS-CoV-2-specific neutralizing antibodies, evolving differently after virus infection and COVID-19 vaccination, which is an important issue to consider in ongoing vaccine strategy improvements.